Investment, rational inattention, and delegation - Assar Lindbeck; Jörgen Weibull (Research Institute of Industrial Economics (IFN), 2017)
We analyze investment decisions when information is costly, with and without delegation to an agent. We use a rational-inattention model and compare it with a canonical signal-extraction model. We identify three "investment conditions". In "sour" conditions, no information is acquired and no investment made. In "sweet" conditions, investment is made "blindly", i.e. without acquiring costly information. In intermediate, "normal" conditions, the decision-maker acquires information and conditions the investment decision upon the information obtained. We investigate if the investor can benefit from employing an agent when the agent's effort and information is private. Not even in the case of a risk neutral agent will the principal perfectly align the agent's incentives with her own at the moment of investment (had the principal known the agent's private information). Optimal contracts for risk neutral agents not only reward good investments but also punishes bad investments. Such contracts include three components: a fixed salary, stocks and options.
Keywords: D01; D82; D86; G11; G23; G30; 330; Investment; rational inattention; signal extraction; principalagent; information acquisition; contract; bonus; penalty